Medical computer vision and Bayesian and graphical models for biomedical imaging : MICCAI 2016 International Workshops, MCV and BAMBI, Athens, Greece, October 21, 2016, Revised selected papers /: MICCAI 2016 International Workshops, MCV and BAMBI, Athens, Greece, October 21, 2016, Revised selected papers. (2017) - Unknown
No abstract available